Coercive Organizational Politics and Organizational Outcomes: An Interpretive Study - Voyer, John J. (Organization Science, 1994)
This study tried to understand how the members of an organization interpreted, in their enacted cognitive schema, the events and processes they enacted during their formation of a new strategy. Participant observation, qualitative interviewing, and cognitive mapping identified many important organizational processes. Among these were pervasive coercive organizational politics, which was retained as an interesting element of the organization's rich cognitive schema. Organization members interpreted politics as being deleterious to morale, as indirectly related to inferior organizational performance outcomes, and as a source of organizational control in the form of negative feedback loops. They also interpreted politics in a paradoxical way—greater levels of political activity led to lower levels of political activity.